27.8k views
4 votes
Guys please answer this. Im in dire need of your help! ):

why can we write 1/a^n=a^-n?

User John Cast
by
5.3k points

2 Answers

4 votes

Explanation:


\frac{1}{ {a}^(n) } = {a}^( - n)

~Math Induction


\:

—Prove that n = 1


\frac{1}{ {a}^(1) } = {a}^( - 1)


(1)/(a) = (1)/(a) \to \sf proved


\:

—Prove that n = k


\frac{1}{{a}^(n)} = {a}^(n)


\frac{1}{{a}^(k)} = {a}^(-k) , k \in \mathbb{R}


\:

—Prove that n = k + 1


\frac{1}{ {a}^(k + 1) } = {a}^( - (k + 1))


\frac{1}{ {a}^(k + 1) } = {a}^( - k) * {a}^( - 1)


\frac{1}{ {a}^(k + 1) } = \frac{1}{ {a}^(k) } * \frac{1}{ {a}^(1) }


\frac{1}{ {a}^(k + 1) } = \frac{1}{ {a}^(k + 1) } \: \: \rm proved


\:

Proved that 1/a^n = a^-n

User Jenson Raby
by
5.9k points
4 votes

Answer:

Try to understand by substitute a number in a and n.

Explanation:

For example,

a=2, n=1

a^n= 2^1= 2


(1)/(2) = 0.5

2^(-1)=0.5

User Unsolved Cypher
by
5.2k points